2020
DOI: 10.1186/s12866-020-01989-z
|View full text |Cite
|
Sign up to set email alerts
|

PhoPQ two-component regulatory system plays a global regulatory role in antibiotic susceptibility, physiology, stress adaptation, and virulence in Stenotrophomonas maltophilia

Abstract: Background Stenotrophomonas maltophilia, an opportunistic pathogen, is ubiquitously present in various environments, signifying its high capability of environmental adaptation. Two-component regulatory system (TCS) is a powerful implement to help organisms to survive in different environments. In clinic, treatment of S. maltophilia infection is difficult because it is naturally resistant to many antibiotics, highlighting the necessity to develop novel drugs or adjuvants. Given their critical and extensively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Expression of the mgtA and mgtCB loci is modulated by the PhoQ/P two-component system, a phosphorylation relay that regulates virulence, pH, osmolality-induced stress, and Mg 2+ deficiency (Fig. 1) [59][60][61]. The membrane receptor PhoQ phosphorylates the transcription factor PhoP when extracellular Mg 2+ concentrations decrease.…”
Section: The Mg 2+ Transporting Atpase Mgta/b and Orthologuesmentioning
confidence: 99%
“…Expression of the mgtA and mgtCB loci is modulated by the PhoQ/P two-component system, a phosphorylation relay that regulates virulence, pH, osmolality-induced stress, and Mg 2+ deficiency (Fig. 1) [59][60][61]. The membrane receptor PhoQ phosphorylates the transcription factor PhoP when extracellular Mg 2+ concentrations decrease.…”
Section: The Mg 2+ Transporting Atpase Mgta/b and Orthologuesmentioning
confidence: 99%
“…Except CpxA which is a histidine kinase, the other 8 proteins are response regulators in two-component regulatory systems. It has been reported that many twocomponent regulatory systems, such as PhoP/PhoQ and EnvZ/OmpR, play important roles in virulence [36][37][38][39]. Thus, the 9 proteins could be potential drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…Except for CpxA that is a histidine kinase, the other 8 proteins are response regulators in two-component regulatory systems. It has been reported that many two-component regulatory systems, such as PhoP/PhoQ and EnvZ/OmpR, play important roles in virulence [32][33][34][35]. Thus, the 9 proteins could be potential drug targets.…”
Section: Discussionmentioning
confidence: 99%